AWARENESS OF MEDICAL APPLICATIONS OF OZONATED WATER THERAPY AMONG DENTAL STUDENTS - Masilamani, Nithyanandham; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Ozone (O3) happens to be a triple atomic particle that comprise three oxygen iotas with an atomic load of 47.98 g/mol. Ozone is a thermokinetic coseismal particle which, contingent upon framework conditions like temperature and weight, has a short half-life and breaks down into sub-atomic oxygen (O2). Ozone is utilized as medication in many conditions. The aim of the study was to assess the awareness of medical applications of ozonated water therapy among dental students. A cross-sectional study was done with a self-administered questionnaire with 10 questions circulated among 100 dental students. The questionnaire assessed the awareness about ozone water therapy in medical applications, their medicinal uses, antinflamatory activity, mechanism of action and side effects. The responses were recorded and analysed.87% of the respondents were not aware of medical uses of Ozone water therapy .73% were not aware of antinflammatory activity of Ozone water therapy.83 % were not aware of the mechanism of action of Ozone water therapy .85% were not aware of side effects of Ozone water therapy. The awareness about the use of Ozone water therapy in medical applications is very less among dental students. Increased awareness programs and sensitization and continuing dental education programs along with greater importance to the curricular modifications should be incorporated to improve the awareness levels.